Bioengineered Efficacy Models of Skin Disease: Advances in the Last 10 Years - Diana Nicole Stanton; Gitali Ganguli-Indra; Arup Kumar Indra; Pankaj Karande (MDPI AG, 2022)
Models of skin diseases, such as psoriasis and scleroderma, must accurately recapitulate the complex microenvironment of human skin to provide an efficacious platform for investigation of skin diseases. Skin disease research has been shifting from less complex and less relevant 2D (two-dimensional) models to significantly more relevant 3D (three-dimensional) models. Three-dimensional modeling systems are better able to recapitulate the complex cell-cell and cell-matrix interactions that occur in vivo within skin. Three-dimensional human skin equivalents (HSEs) have emerged as an advantageous tool for the study of skin disease in vitro. These 3D HSEs can be highly complex, containing both epidermal and dermal compartments with integrated adnexal structures. The addition of adnexal structures to 3D HSEs has allowed researchers to gain more insight into the complex pathology of various hereditary and acquired skin diseases. One method of constructing 3D HSEs, 3D bioprinting, has emerged as a versatile and useful tool for generating highly complex HSEs. The development of commercially available 3D bioprinters has allowed researchers to create highly reproducible 3D HSEs with precise integration of multiple adnexal structures. While the field of bioengineered models for study of skin disease has made tremendous progress in the last decade, there are still significant efforts necessary to create truly biomimetic skin disease models. In future studies utilizing 3D HSEs, emphasis must be placed on integrating all adnexal structures relevant to the skin disease under investigation. Thorough investigation of the intricate pathology of skin diseases and the development of effective treatments requires use of highly efficacious models of skin diseases.